2020
DOI: 10.3390/ijerph17249584
|View full text |Cite
|
Sign up to set email alerts
|

Mortality- and Health-Related Factors in a Community-Dwelling of Oldest-Older Adults at the Age of 90: A 10-Year Follow-Up Study

Abstract: Mortality is obviously intended for epidemiological studies of community-dwelling older adults. There are several health-related factors associated with nutritional status and mortality. The aim of this study was to elucidate the risk factor for mortality in community-dwelling oldest-older adults at the age of 90 and clarify the structure of health-related factors associated with mortality. A 10-year follow-up study was performed for 93 subjects at the age of 90. The mean and median of their survival days were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 115 publications
0
2
0
Order By: Relevance
“…13 There were more female patients included in the study, which is due to females tend to live longer but are in poorer health than males late-in-life. 14,15 In general, this is probably because the prevalence of osteoporosis is much higher in women than in men and suffers the majority of osteoporotic bone fractures. 16,17 In this study, we also found most patients had their fractures occurring at home, taking approximately three-fifths of the overall fractures.…”
Section: Discussionmentioning
confidence: 99%
“…13 There were more female patients included in the study, which is due to females tend to live longer but are in poorer health than males late-in-life. 14,15 In general, this is probably because the prevalence of osteoporosis is much higher in women than in men and suffers the majority of osteoporotic bone fractures. 16,17 In this study, we also found most patients had their fractures occurring at home, taking approximately three-fifths of the overall fractures.…”
Section: Discussionmentioning
confidence: 99%
“…In China, the legal age for marriage is 20 for women but 22 for men, which may account for the higher marital SES-score in youth women. However, due to the longer life expectancy of women, 23 old women were more likely to lose their partner than old men. Thus, the gender gap in marital status reversed with age.…”
Section: Discussionmentioning
confidence: 99%